KELIMPAHAN BAKTERI SALURAN PENCERNAAN IKAN NILEM (Osteochilus vittatus) YANG DIBERI PAKAN DENGAN SUPLEMENTASI GARAM (NaCl) - Emyliana Listiowati; H. Syakuri; A. Ekasanti; D. Nugrayani; D. Wisudyanti; R. Oktavia (Jurnal Perikanan Pantura (JPP), 2023)
Bonylip barb fish is an aquaculture commodity that has the potential to be developed in Banyumas district. In its cultivation activities, bonylip barb are able to consume artificial feed well. The feed consumed will affect the digestive condition. The fish digestive tract is a complex system whose main functions are digestion and absorption. Nutrient absorption in intestinal cells is influenced by active transport of Na+ (sodium) ions. Na+ and Cl ion levels are obtained through water and feed. This study aims to determine the effect of salt supplementation in commercial feed with different concentrations on bacterial abundance. The research was carried out experimentally with salt supplementation doses (0%, 1%, 2%, 3%, and 4%; w/w) to be applied to bonylip barb seeds (5-7 cm) for 60 days. Research parameters include bacterial abundance, positive and negative gram tests. The results showed that the treatment with the addition of 2% NaCl gave a total number of bacteria that tended to be higher than the control (0% NaCl). The total number of bacteria in the digestive tract of Nilem fish that were given NaCl addition to the feed ranged from 3.78 Â± 6.27 x 106 CFU/gram to 32.04 Â± 19.51 x 106 CFU/gram. The addition of NaCl affects the proportion of gram positive and negative in the digestive tract of tilapia (Oreochromis niloticus). Gram positive bacteria tended to dominate in the 2% NaCl treatment at 69.99% and gram negative bacteria at 21.69%.